PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL ADOBE FLASH PADA PELAJARAN GEOGRAFI KELAS X DI SMA NEGERI 1 ROTE BARAT LAUT - Mbau, Diana; Pamungkas, Bella Theo Tomi; Hasan, Muhammad Husain (Universitas Nusa Cendana, 2023)
The research objectives here are; to determine the development of adobe flash CS6-based learning media and to find out student learning outcomes after using adobe flash CS6-based learning media. This type of research is development research (R&D), the stages of R&D research include potential and problems, data collection, product design, design validation, design revisions, product trials, product revisions, usage trials. The variables of this study: the level of feasibility, student responses to learning media and student learning outcomes. Collection techniques include observation, questionnaires, documentation and tests. The results of the adobe flash CS6-based learning media research in the form of an interactive CD developed through the R&D research stages. Validation by experts Shows that interactive CDs are feasible to use in learning with an average score of 93% and material expert validation states that it is feasible with a feasibility percentage of 79%. The results of student responses as media users rate very feasible with a percentage of 89%. Cognitive learning outcomes of students at SMA Negeri 1 Rote Barat Laut increased, before using the media the average test score was 62.35 and after using adobe flash CS6-based learning media it became 89% The conclusion of this study was adobe flash CS6-based learning media in CD form. interactive is declared feasible and can improve student learning outcomes. This means that student learning outcomes on the hydrosphere subject matter increased after using adobe flash CS6-based learning media.